Transversus abdominis plane block in two calves undergoing umbilical herniorrhaphy. Issue 1 (16th May 2017) - Zoff, Aurora; Dugdale, Alex; Coates, A N; Rioja, Eva
Abstract : A transversus abdominis plane (TAP) block was performed in two calves undergoing umbilical hernia repair. Both calves were in good health and body condition and were anaesthetised using standard anaesthesia protocols. After placement in dorsal recumbency, the abdomen was scanned with an 11‐MHz linear array probe from the last rib to the iliac crest to identify the abdominal musculature comprising the external and internal abdominal oblique muscles and the transversus abdominis (TA). The needle (SonoTAP cannula 22G×50 mm; Pajunk) was advanced using an in‐plane technique, and a volume of 0.3 ml/kg was injected after a test dose. No obvious reduction of isoflurane requirements was apparent and one of the calves required rescue analgesia. The calves recovered uneventfully from anaesthesia. This case report discusses the advantages of the TAP block over the paravertebral block, discusses the risks associated with TAP blocks and highlights the importance of training in ultrasound‐guided techniques.